MODIFIKASI DAN INOVASI OLAHAN RINGAN BAKSO AYAM MENJADI KERIPIK BASRENG OLAHAN PROGRAM MBKM MAHASISWA INDO GLOBAL MANDIRI - Mutiara Puteri, Adinda; Lestari Setia Ningrum, Ayu; Hertati, Lesi; Terttiaavini; Heryati, Agustina; Asmawati (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2021)
Fried meatballs, commonly known as basreng, are a popular snack made from thinly sliced and fried processed meatballs. Typically served with a spicy seasoning and garnished with orange leaf slices, basreng has gained popularity, especially among young people. The objective of creating snack products using processed basreng is to introduce new innovations to the community surrounding the UIGM Palembang Campus, transforming viral basreng chips into a more modern food option. The manufacturing process for this basreng product differs from the traditional version. It is thinly shaped like chips instead of the usual stick form and includes a variety of spiciness levels and garnished with orange leaf slices, attracting buyers' interest. The marketing strategy involves utilizing digital marketing, such as online shops, to achieve widespread sales across various areas through social media applications, thereby increasing product demand. Consequently, the production of this innovative basreng can inspire young people to establish new Micro, Small, and Medium Enterprises (MSMEs) specializing in selling basreng products.